Metaphors in the analysis of the Polish socio-economic transformation in the 1990s: problems of sociological imagination and creativity - Kamińska-Berezowska, Sławomira; Słupik, Tomasz (Creativity Studies, 2024)
A primary assumption made for reflections presented in this article is the possibility of describing social reality using metaphors and their crucial role in creative thinking. The analysis is based on the interdisciplinary research project Images of the Polish Socio-Economic Transformation in the Eyes of Foreign Researchers in the Context of Their Social Roles and Intercultural Communication (2023 – now). The article references three metaphorical images of the Polish socio-economic transformation of the 1990s. It shows how they reflect the diversity of social reality and the selective character of its perception. Due to the use of metaphors in describing the analyzed process, it was possible to highlight its specific characteristics, which is typical of this approach. Besides, the article indicates that participants of the socio-economic transformations can perceive them differently than distanced external researchers with different baggage of personal and epistemological experience. Therefore, the article focuses on this rich diversity in the perception of social reality and the creative thinking associated with it.